Development of PD measurement, analysis and FRA techniques for power apparatus - Birlasekaran, Sivaswamy. (2008)
This research report presents the details on two specific condition monitoring techniques which can be effectively used in different power utilities of Singapore and other Asian countries. In Singapore, the preferred condition monitoring method must be non-intrusive to high voltage side, preferably on-line mode without switching off the operating apparatus, and not disconnecting with the rest of the connected apparatus in the power network, able to provide some condition indicating parameters to evaluate the asset value and reliable operation and able to identify the type of developing fault and its location. While from University side, the requirement is to generate graduate students for industry and teaching with enough number of standard research publications and to develop some research facilities in the laboratory.